Efeito cardioprotetor do apha-terpineol em ratos infartados - Paulino, Emanuel Tenório (2019)
Introduction: Myocardial infarction is the most common clinical outcome associated with mortality and morbidity of cardiovascular diseases previously. The complexity of infarction pharmacotherapy associated with the lack of cardioprotective drugs hás encouraged the development of new cardioprotection strategies. Thus, compounds of natural have been represented candidate molecules for new drugs. In this context, α-terpineol (TPN) is a cyclic monoterpene of natural origin that exhibits cardiovascular actions such as vasorelaxant endothelium-dependent and acute antihypertensive in SHR type rats. TPN is a major compound of essential oil of Protium heptaphylum that produce cardiovascular effects as vasorelaxant activity. However, cardioprotective action of TPN remains unknown. Objective: Evaluate the cardioprotective effect of TPN on acute myocardial infarction in rats. This study was approved by ethics committee nº09/2015. Methods: Wistar and SHR rats, were allocated on 7 experimental groups, were pre-treated for 15 days orally and induced to infarction by isoproterenol (ISO): (G1= saline 0.9%); (G2= Infarcted saline 0,9%); (G3= TPN 25 mg/kg); (G4=TPN 50 mg/kg); (G5=TPN 75 mg/kg); (G6=TPN 50 mg/kg without ISO) and (G7=Nifedipine (NIF) 3 mg/kg). On 16º day, rats were anesthetized (Ketamine 80 mg/kg + Xylazine 4 mg/kg i.p.) and biochemical, morphometric, hemodynamic, baroreflex and electrocardiographic tests were performed. Cardiovascular fragments were used to determine calcium levels and to assess vascular reactivity. Additionally a curve dose-response in hypertensive animals non-anesthetized with TPN was realized. Molecular docking was also accomplished. Results: TPN increased the survival of animals to induced infarction, reduced necrosis area of the myocardium, prevented changes on electrocardiographic tests and inhibited the release of cardiac markers. Furthermore, TPN inhibited isoproterenol-induced elevation of heart rate. TPN prevented the imbalance on calcium levels in the ventricles and aorta. In addition, TPN produced coronary dilatation and endothelial neovascularization in vessels of rats. TPN also changes of the potency and maximal effect of vascular reactivity of hypertensive and infarcted rats. TPN induced dose-dependent intravenous bradycardia, which was significantly attenuated in the presence of a muscarinic receptor blocker. Molecular docking studies show that TPN has an electronic affinity for muscarinic M2 receptors but also on calcium-dependent voltage channels L type producing nifedipine-like blocking. Conclusion: Alpha-terpineol produces cardioprotection in rats, and its mechanisms appear to involve cardiac M2 receptors and the blockage on the VOCC's. TPN may be a cardioprotective drug candidate molecule. However, further studies are needed to elucidate the mechanisms of this action.